Association of human papillomavirus and p16 status with mucositis and dysphagia for head and neck cancer patients treated with radiotherapy with or without cetuximab: Assessment from a phase 3 registration trial - Bonner, James A. (Eur J Cancer, 2016)
BACKGROUND: Mucositis and dysphagia are common adverse effects of radiotherapy (RT) treatment of locally advanced squamous cell cancer of the head and neck (LA-SCCHN). Chemotherapy added to RT increases survival rates but causes worse mucositis and dysphagia. The aim of this analysis was to assess the impact of p16 status on mucositis, dysphagia, and feeding tube use in LA-SCCHN among patients treated with RT ± cetuximab in the phase 3 IMCL-9815 trial. METHODS: Patients received RT plus weekly cetuximab or RT alone. Subgroup analyses were conducted on patients with p16-positive (n = 75) or p16-negative (n = 106) oropharyngeal cancer (OPC), as determined by immunohistochemical analysis. The onset and duration of mucositis and dysphagia by treatment arm and p16 status were displayed using Kaplan–Meier curves and the log-rank test. P values for the incidence of mucositis and dysphagia were calculated using the Fisher exact test. Feeding tube use was assessed as the percent of patients reporting use. RESULTS: The baseline characteristics of patients treated with RT ± cetuximab were similar in both the p16-positive and p16-negative OPC subgroups. Patients within the p16-positive OPC subgroup had higher Karnofsky scores and were more likely to have stage T1–T3 cancer and be from the United States. Regardless of p16 status, there was no difference in the onset or duration of grade 3/4 mucositis or dysphagia in patient receiving RT plus cetuximab compared with those receiving RT alone. In the overall population, and the p16-positive and p16-negative OPC subpopulations, feeding tube use was not different for patients receiving RT plus cetuximab compared with RT alone. CONCLUSION: Regardless of p16 status, the addition of cetuximab to RT did not alter the incidence, time to onset, severity, or duration of mucositis and dysphagia and did not impact the frequency of feeding tube use.